Implementation of Internal Quality Assurance System Policy and its Impact on School Performance: A Case Study at SDIT Aya Sophia Islamic School - Siswadi, Agus; Sudrajat, Jajat; Afandi, Richad Dedi Syahbudin; Dahlan, Rudiyanto; Khori, Ahmad (International Journal of Social and Management Studies, 2025)
Education quality assurance is a crucial element in building an adaptive and sustainable education system. This study aims to analyze the implementation of the Internal Quality Assurance System (SPMI) policy and its impact on school performance at Aya Sophia Islamic School. Using a qualitative approach and single case study method, data were collected through in-depth interviews, participatory observation, and documentation study. The findings show that the implementation of SPMI through the PPEPP cycle (Planning, Implementation, Evaluation, Control, and Improvement) is carried out in a participatory and contextual manner, with the active involvement of the principal, teachers, quality team, and parents. Positive impacts are seen in the improvement of students’ academic achievement, parents’ satisfaction and the effectiveness of school governance. However, challenges are still found in the aspects of documentation and integration of quality indicators. This study makes a theoretical contribution to the development of local context-based education policy implementation models and presents practical and managerial implications for improving the quality of education in integrated Islamic schools.